Biodegradable brush-shaped polymer with two annular surfaces and preparation method thereof

By introducing PCL and POEGMA chains into the ring brush polymer, a biodegradable two-sided ring brush polymer is formed, which solves the problem of low drug loading rate and achieves efficient drug carrier performance and stable nano micelle formation.

CN119463060AActive Publication Date: 2025-02-18PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310998278.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18
Estimated Expiration
2043-08-09

AI Technical Summary

Technical Problem

Existing ring brush polymers have low drug loading rates and are not suitable for use as drug sustained release carrier materials.

Method used

By using biodegradable macromolecule PCL as the cyclic macromolecule core and the POEGMA chain with good biocompatible biocompatible as the hydrophilic chain segment as the cyclic outer core, a biodegradable two-sided ring brush-shaped polymer is formed, which is in The aqueous solution can self-assemble to form stable nano micelles with hydrophilic shells and hydrophobic cores.

Benefits of technology

The bioavailability of anti-cancer drugs has been improved, and the drug loading rate and encapsulation rate have been significantly improved, and the nano micelles formed have good stability and drug protection effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463060A_ABST
    Figure CN119463060A_ABST
Patent Text Reader

Abstract

The invention discloses a biodegradable two-sided ring brush-shaped polymer and a preparation method thereof.The two-sided ring brush-shaped polymer has a structure shown in the formula I. An annular inner core is a biodegradable macromolecule PCL, an annular outer core is a POEGMA chain with good biocompatibility and serves as a hydrophilic chain segment, and the annular two-sided ring brush-shaped polymer is formed; the polymer can be self-assembled in an aqueous solution to form a stable nano-micelle with a hydrophilic shell and a hydrophobic core, and the nano-micelle is high in drug loading rate and high in encapsulation efficiency. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer technology, in particular to a biodegradable two-sided ring brush polymer and a preparation method thereof. Background Art

[0002] In recent years, polymers with advanced topological structures have become one of the research hotspots in the biomedical field because of their unique properties that are superior to traditional linear polymers. Among them, ring-brush polymers have attracted widespread attention from researchers due to their nanoscale size, hyperbranched structure, simultaneously functionalized ring core and polymer surface, and simpler preparation methods compared to dendrimers. Ring-brush polymers (amphiphilic copolymers) can self-assemble into unique core-shell structure micelles in aqueous solution because of their hydrophilic / hydrophobic polymer segments. They can prevent the off-target behavior of the encapsulated anticancer drugs, reduce the damage of drugs to normal tissues and organs of the human body, and protect the drugs from being affected by the surrounding sensitive environment and degrading prematurely.

[0003] For example, the third chapter of Lanzhou University's 2018 master's thesis "Construction of two-sided ring brush-shaped amphiphilic block copolymers and research on their performance as drug carriers" discloses a two-sided ring brush-shaped amphiphilic copolymer P(OEGMA) m -bP(HEMA-g-OCLh) n The copolymer can form self-assembled micelles with a size of about 200nm in water. The results of in vitro drug loading and release behavior experiments show that the drug loading rate is 8.61% and the encapsulation rate is 86.09%, which has excellent potential as a drug carrier. However, the particle size of the self-assembled micelles formed by the polymer in water is large, and the circulation time of the micelles in the blood after drug loading is short, which cannot effectively deliver drugs to tumor tissues.

[0004] Polycaprolactone (PCL) is a very important type of synthetic biomaterial. Due to its good biodegradability, excellent biocompatibility, low immunity and good mechanical properties, PCL is non-toxic and is a type of biomedical material approved by the US Food and Drug Administration (FDA). It has been widely used in surgical sutures, bone fixation, tissue engineering and drug carriers. In response to the above problems, researchers have tried to introduce PCL into polymers.

[0005] For example, the fourth chapter of Lanzhou University's 2018 doctoral dissertation "Synthesis, self-assembly behavior and in vitro performance of novel cyclic brush polymers as anticancer drugs" discloses an amphiphilic cyclic brush copolymer P (HEMA-g-PCL-POEGMA), which can form stable core-shell corona structure micelles in water, with a small particle size of about 40nm and a drug loading rate of 4.20%. However, the drug loading rate of the polymer disclosed in the document is low.

[0006] The journal article "Synthesis and Characterization of Amphiphilic Cyclic Poly(caprolactone-b-vinylpyrrolidone)" discloses a controllable synthesis method of amphiphilic cyclic poly(caprolactone-b-vinylpyrrolidone) block copolymers (Cyclic-PCL-b-PVP). Compared with linear poly(caprolactone-b-vinylpyrrolidone) (Cyclic-PCL-b-PVP), the corresponding cyclic block copolymers have significantly improved thermal stability and changed hydrophilicity. However, the polymer disclosed in this scheme only discusses the synthesis of the polymer and the influence of its topological structure on its thermal properties and hydrophilicity, and does not conduct in-depth research on drug delivery.

[0007] Chinese patent CN103709691A discloses a biodegradable cross-linked polymer, which is a cross-linked polymer network obtained by introducing a cross-linkable active group at the end of a degradable polymer prepolymer with two or more arms, and then subjecting it to thermal polymerization and / or light irradiation treatment. The elastic modulus is between 10MPa and 1500MPa, the degradation rate is between 3 months and 36 months, the reaction is simple, and it is easy to prepare and is used in the field of medical devices. However, the polymer disclosed in the scheme is a multi-arm cross-linked polymer, which is not suitable for use as a drug sustained-release carrier material.

[0008] The journal article "Synthesis and Self-Assembly of Amphiphilic Cyclic Brush Copolymers with Core-Shell-Crown Structure" discloses the preparation of cyclic brush polymer P (HEMA-g-PCL-POEGMA), specifically using PCL and POEGMA as the hydrophobic and hydrophilic segments of the amphiphilic cyclic brush copolymer, both of which have good biocompatibility, and PCL also has good biodegradability. However, the drug loading rate of the polymer disclosed in the document is low. Summary of the invention

[0009] In view of the problems existing in the prior art and the directions for improvement, the present invention provides a biodegradable two-sided ring brush polymer, which forms a ring-shaped two-sided ring brush polymer by using the biodegradable macromolecule PCL as the inner core of the ring-shaped macromolecule and the POEGMA chain with good biocompatibility as the hydrophilic chain segment as the outer core of the ring. The polymer can self-assemble in aqueous solution to form stable nano-micelles with a hydrophilic outer shell and a hydrophobic inner core, so as to solve the technical problems of the existing ring brush polymers such as low drug loading rate or unsuitability for use as drug sustained-release carrier materials.

[0010] To achieve the above object, the present invention provides a biodegradable two-sided ring brush polymer, characterized in that it has a structure shown in Formula I:

[0011]

[0012] Among them, m=a natural number from 10 to 50; n=a natural number from 5 to 20, and p=a natural number from 2 to 15.

[0013] The present invention also provides a method for preparing a biodegradable two-sided ring brush polymer, comprising the following steps:

[0014]

[0015] Step 1, propargyl alcohol and caprolactone undergo a ring-opening polymerization reaction to generate a polymer shown in formula II;

[0016] Step 2, the polymer represented by formula II is subjected to substitution reaction with 2-bromoisobutyryl bromide to generate a polymer represented by formula III;

[0017] Step 3, the polymer represented by formula III is subjected to an atom transfer radical polymerization reaction with 2-hydroxyethyl methacrylate to generate a polymer represented by formula IV;

[0018] Step 4, the polymer represented by formula IV is subjected to an azidation reaction with sodium azide to generate a polymer represented by formula V;

[0019] Step 5, the polymer represented by formula V undergoes a click chemistry reaction to generate a polymer represented by formula VI;

[0020] Step 6, the polymer represented by formula VI is subjected to a substitution reaction with 2-bromoisobutyryl bromide to generate a polymer represented by formula VII;

[0021] Step 7, atom transfer radical polymerization of the polymer represented by formula VII and oligo(ethylene glycol methoxymethylacrylate) to generate a biodegradable two-sided ring brush polymer represented by formula I;

[0022] Among them, m=a natural number from 10 to 50, n=a natural number from 5 to 20, and p=a natural number from 2 to 15.

[0023] Optionally, in the method for preparing a biodegradable two-sided ring brush polymer provided by the present invention, in step 1, under anaerobic conditions, propargyl alcohol and caprolactone (ε-CL) are subjected to a ring-opening polymerization reaction in the presence of a catalyst, wherein the molar ratio of propargyl alcohol, caprolactone and the catalyst is 1:15-60:0.02-0.1; preferably, the catalyst is a metal organic compound such as stannous octoate (Sn(Oct)2), stannous isooctanoate or tetraphenyltin.

[0024] The reaction conditions in step 1 recommended by the present invention are as follows: after uniformly mixing propargyl alcohol, ε-CL and Sn(Oct)2 in a molar ratio of 1:15-60:0.02-0.1, deoxygenating, stirring and reacting at 40-150° C. for 1-6 hours, and vacuum drying, a polymer (alkynyl-PCL-OH) shown in formula II is obtained, and the reaction formula is as follows:

[0025]

[0026] Optionally, in the method for preparing the biodegradable two-sided ring brush polymer provided by the present invention, in step 2, the polymer represented by formula II is reacted with 2-bromoisobutyryl bromide (abbreviated as i BuBr) is subjected to substitution reaction under alkaline conditions, wherein the molar ratio of the polymer represented by formula II, the base and 2-bromoisobutyryl bromide is 1:4-16:3-12; preferably, the base is an organic weak base such as triethylamine and pyridine.

[0027] The reaction conditions in step 2 recommended by the present invention are as follows: the polymer represented by formula II, triethylamine and i BuBr was added to DCM (dichloromethane), stirred at room temperature for 36 to 48 hours, and then dried in vacuo to obtain a polymer (alkynyl-PCL- i BuBr), the reaction formula is as follows:

[0028]

[0029] Optionally, in the method for preparing a biodegradable two-sided ring brush polymer provided by the present invention, in step 3, under anaerobic conditions, the polymer shown in formula III and 2-hydroxyethyl methacrylate (HEMA) are subjected to an atom transfer radical polymerization reaction in the presence of a catalyst; preferably, the catalyst comprises CuBr and a ligand, and the ligand is selected from 2,2′-bipyridine (bpy) or tris(2-dimethylaminoethylamine) (Me6TREN); more preferably, the molar ratio of the polymer shown in formula III, HEMA, bpy and CuBr is 1:8 to 25:2:1, and the molar ratio of the polymer shown in formula III, HEMA, tris(2-dimethylaminoethylamine) and CuBr is 1:8 to 25:1:1.

[0030] The reaction conditions in step 3 recommended by the present invention are as follows: the polymer (alkynyl-PCL- i BuBr), HEMA, bpy, and CuBr are mixed evenly in a mixed solution of isopropanol and DMF, deoxygenated, stirred and reacted at 50-70° C. for 2-4 hours, dialyzed, and freeze-dried to obtain a polymer (alkyne-PCL-b-PHEMA) of formula IV. The reaction formula is as follows:

[0031]

[0032] Optionally, in the method for preparing a biodegradable two-sided ring brush polymer provided by the present invention, in step 4, the molar ratio of the polymer represented by formula IV to sodium azide is 1:10-50.

[0033] The reaction conditions in step 4 recommended by the present invention are as follows: the polymer represented by formula IV and NaN3 are dissolved in a mixed solution of a small amount of DMF and water at a molar ratio of 1:10-50, stirred and reacted at 40-60° C. for 24-48 hours, dialyzed and freeze-dried to obtain a polymer represented by formula V (alkynyl-PCL-b-PHEMA-N3), and the reaction formula is as follows:

[0034]

[0035] Optionally, in the method for preparing a biodegradable two-sided ring brush polymer provided by the present invention, in step 5, under anaerobic conditions, the polymer shown in formula V undergoes a click chemistry reaction under the catalysis of N′,N′,N′,N′,N′-pentamethyldiethylenetriamine (PMDETA) and CuBr, preferably, the molar ratio of the polymer shown in formula V, PMDETA and CuBr is 1:10~50:10~50.

[0036] The reaction conditions in step 5 recommended by the present invention are as follows: the polymer represented by formula V, PMDETA and CuBr are dissolved in a large amount of DMF solution at a molar ratio of 1:10-50:10-50, mixed evenly, deoxygenated, stirred and reacted at 80-120° C. for 24-48 hours, dialyzed and freeze-dried to obtain a polymer represented by formula VI, and the reaction formula is as follows:

[0037]

[0038] Optionally, in the method for preparing a biodegradable two-sided ring brush polymer provided by the present invention, in step 6, the polymer represented by formula VI is subjected to a substitution reaction with 2-bromoisobutyryl bromide under alkaline conditions, wherein the molar ratio of the polymer represented by formula VI, the base and 2-bromoisobutyryl bromide is 1:2 to 8:2 to 6; preferably, the base is an organic weak base such as triethylamine and pyridine.

[0039] The reaction conditions in step 6 recommended by the present invention are as follows: the polymer represented by formula VI, triethylamine and i BuBr is added to dichloromethane, stirred and reacted at room temperature for 36 to 48 hours, and vacuum dried to obtain a polymer represented by formula VII. The reaction formula is as follows:

[0040]

[0041] Optionally, in the method for preparing a biodegradable two-sided ring brush polymer provided by the present invention, in step 7, under anaerobic conditions, the polymer shown in formula VII and oligo(ethylene glycol methoxymethylacrylate) (OEGMA) are subjected to atom transfer radical polymerization under the catalysis of 2,2′-bipyridine (bpy) and CuBr, wherein the molar ratio of the polymer shown in formula VII, oligo(ethylene glycol methoxymethylacrylate), bpy and CuBr is 1:5 to 30:2:1.

[0042] The reaction conditions in step 7 recommended by the present invention are as follows: the polymer represented by formula VII, OEGMA, bpy, and CuBr are dissolved in a DMF solution at a molar ratio of 1:5 to 30:2:1, deoxygenated, stirred and reacted at 50 to 70° C. for 0.5 to 1 h, dialyzed, and freeze-dried to obtain a biodegradable two-sided ring brush-shaped polymer represented by formula I, and the reaction formula is as follows:

[0043]

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The biodegradable two-sided ring brush polymer provided by the present invention is a two-sided structural polymer, wherein the hydrophobic surface is a PCL structure and is directly located on the ring, and the hydrophilic surface is a P (HEMA-g-POEGMA) structure and is located on the side chain of the ring. Each polymer fragment in the polymer structure has a high drug loading rate and encapsulation rate within an appropriate degree of polymerization range, which can reach 8.90% and 89.25% respectively, thereby effectively improving the bioavailability of anticancer drugs and having application prospects as a drug carrier.

[0046] 2. The biodegradable two-sided ring brush polymer provided by the present invention can form self-assembled micelles with a size of about 40 nm in water and has good stability in phosphate buffer solution (PBS, pH 7.4, ionic strength 150 mM).

[0047] 3. The preparation method of the biodegradable two-sided ring brush polymer provided by the present invention is simple to operate and has mild reaction conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is the NMR characterization image of the biodegradable two-sided ring brush polymer prepared in Example 1 of the present invention;

[0049] Figure 2 This is a graph showing the particle size variation of the biodegradable two-sided ring brush-shaped polymer micelles prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0050] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.

[0051] Example 1 Preparation of biodegradable two-sided ring brush polymer

[0052] 1) Weigh 0.1g of propargyl alcohol and 6.80g of ε-CL into a reaction tube, freeze-pump-thaw to deoxygenate three times, seal the reaction tube, and stir vigorously in an oil bath at 110℃ for about 8min to make it homogeneous. After freezing, add 28.936mg Sn(Oct)2 (stannous octoate) under nitrogen protection, freeze-pump-thaw to deoxygenate three times again, seal, and react at 110℃ for 2h. After the reaction is completed, wait for the reaction tube to cool, add a small amount of THF to dilute the product, precipitate with excessive ice-anhydrous methanol, centrifuge to obtain a crude product, dilute with THF again, precipitate with ice-anhydrous methanol and centrifuge, repeat the process three times, and finally vacuum dry to obtain a white flocculent solid (polymer shown in Formula II), perform nuclear magnetic hydrogen spectrum detection on the substance, and find the corresponding characteristic peaks in the polymer from the corresponding hydrogen spectrum, and then calculate the degree of polymerization of polycaprolactone m=28.

[0053] 2) Weigh 2.0 g of the polymer represented by the above formula II (m = 28) and dissolve it in 5 mL of anhydrous DCM and stir evenly. Place the mixture in an ice bath, add 0.7088 g of triethylamine, stir for about 10 min, and then add 1.1209 g of iBuBr, stirred for 20 min, and then stirred at room temperature for 48 h. After the reaction, the solvent was dried by spin drying, THF was added to dissolve, and the insoluble matter was removed by suction filtration. The filtrate was precipitated in excess ice anhydrous methanol and centrifuged to obtain a crude product, which was diluted with THF again, precipitated with ice anhydrous methanol and centrifuged. The process was repeated three times, and finally vacuum dried to obtain a light yellow solid, i.e., the polymer shown in formula III (m=28, polycaprolactone PCL- i BuBr).

[0054] 3) Weigh 4.4g of the polymer shown in Formula III obtained above, 1.78g of monomer 2-hydroxyethyl methacrylate, and 0.625g of bipyridine, dissolve in 0.15mL DMF and 2.0mL isopropanol, and place in a polymerization tube after complete dissolution, freeze-pump-thaw deoxygenation three times, add 0.287g of CuBr solid powder under nitrogen protection, continue freeze-pump-thaw cycle three times, seal the tube, and react at 60°C for 4h. After the reaction is completed, quench with air, add a small amount of THF to dilute, precipitate with excessive ice anhydrous ether, centrifuge, dissolve in a small amount of DMF, dialyze against water for 48h, and freeze-dry to obtain a white powder, i.e., the polymer shown in Formula IV (i.e., an amphiphilic polymer with a bromine group as the terminal group), and perform nuclear magnetic hydrogen spectrum detection on the substance, and find the corresponding characteristic peaks in the polymer from the corresponding hydrogen spectrum, and then calculate the degree of polymerization of the hydrophilic segment n=8.

[0055] 4) Weigh 1.3 g of the polymer represented by formula IV (n=8) and dissolve it in 5 mL of DMF. Then weigh 0.5 g of NaN3 and dissolve it in distilled water. Pour the mixture into a round-bottom flask, seal it, mix well, stir and react at 45°C for 48 h. After dialysis and freeze-drying, a white powder solid is obtained, i.e., the polymer represented by formula V (amphiphilic polymer with an azide group as the terminal group).

[0056] 5) Pour 750 mL of DMF into a 1L three-necked flask, heat to 100°C with stirring, and introduce high-purity nitrogen to remove oxygen. About 1 hour later, add 0.3466 g of PMDETA and 0.2844 g of CuBr powder into the flask. Dissolve 0.35 g of the polymer solid represented by formula V in 10 mL of DMF, slowly inject it into the three-necked flask after deoxygenation, and continue to react for 24 hours after injection. After the reaction is completed, most of the DMF solvent is evaporated, and the crude product is dialyzed against water for 48 hours. After freeze-drying, a white powder solid is obtained, which is the polymer represented by formula VI.

[0057] 6) Weigh 0.5g of the polymer shown in formula VI and dissolve it in 5mL of anhydrous DCM, and stir evenly. Place the mixture in an ice bath, add 1.212g of triethylamine, stir for about 10min, then add 2.07g of 2-bromoisobutyryl bromide, stir for 20min, and then stir at room temperature for 48h. After the reaction is completed, the solvent is dried, THF is added to dissolve, and the insoluble matter is removed by suction filtration. The filtrate is precipitated in excess ice anhydrous methanol, centrifuged to obtain a crude product, diluted with THF again, precipitated and centrifuged in ice anhydrous methanol, and the process is repeated three times. Finally, vacuum drying is performed to obtain a light yellow solid, i.e., the polymer shown in formula VII (a cyclic amphiphilic polymer with a bromine end group).

[0058] 7) Weigh 0.1g of the polymer shown in formula VII and dissolve it in a mixed solution of 9mL of anisole and DMF (the volume ratio of anisole to DMF is 1:2), then add 0.267g of monomer OEGMA and 0.0078g of bipyridine, mix well, and transfer to a polymerization reaction tube. After three freeze-pump-thaw cycles using an oil pump, quickly add 0.5577g of CuBr powder under nitrogen protection, continue to freeze-pump-thaw cycles three times, seal, and place in a 60°C oil bath pot to stir and react for about 30 minutes. After the reaction is completed, quench with air, precipitate with excess ice anhydrous ether, centrifuge, dialyze for 48 hours to remove the copper catalyst and unreacted monomers, and freeze-dry to obtain a biodegradable two-sided ring brush polymer shown in formula I. The polymer was subjected to nuclear magnetic hydrogen spectrum detection, as shown Figure 1 As shown, the corresponding characteristic peaks in the polymer are found from the corresponding hydrogen spectrum, and then the degree of polymerization of OEGMA p=8 is calculated.

[0059] Embodiment 2-4

[0060] The preparation methods of the biodegradable two-sided ring brush polymer provided in Examples 2-4 are similar to those in Example 1, except that the amount of materials used in each step is different, as shown in Table 1 below.

[0061] Comparative Examples 1-3

[0062] The preparation methods of the biodegradable two-sided ring brush polymer provided in Comparative Examples 1-3 are similar to those in Example 1, except that the amount of materials used in each step is different. See Table 1 below for details.

[0063] Comparative Example 4

[0064] This comparative example provides a biodegradable two-sided ring brush polymer, and the specific reaction formula is as follows:

[0065]

[0066] The preparation method is as follows:

[0067] 1) Dissolve 7.2 g of propargyl alcohol and 18.1 mL of triethylamine in 100 mL of anhydrous dichloromethane, stir under nitrogen and cool to 0 °C, then slowly drop 16.4 mL of i After the addition of BuBr, the reaction was carried out at 0°C for a period of time, and then continued at room temperature for 24 hours. The product was vacuum filtered to remove insoluble matter, extracted three times with saturated sodium chloride, then extracted once with ultrapure water, and then dried with anhydrous magnesium sulfate, and distilled under reduced pressure to obtain a small molecule initiator.

[0068] 2) Weigh 2.45g HEMA, 0.483mg of the above small molecule initiator and 0.74g bpy and dissolve them in a mixed solvent of 0.3mL DMF and 3.2mL isopropanol. After complete dissolution, place in a polymerization tube, freeze-pump-thaw to deoxygenate three times, add 0.34g CuBr solid powder under nitrogen protection, continue freeze-pump-thaw cycle three times, seal the tube, and react at 65℃ for 2h. After the reaction is completed, quench with air, add a small amount of DMF to dilute, precipitate with excess ice anhydrous ether, centrifuge, dissolve in a small amount of DMF, dialyze against water for 48h, and obtain a white powder after freeze-drying. The degree of polymerization of PHEMA a=8 can be calculated by nuclear magnetic resonance.

[0069] 4) Weigh 0.2 g of the above white powder solid and 20 equivalents of sodium azide, dissolve in 10 mL of a water / DMF mixed solvent with a volume ratio of 1 / 4, mix well and place in a 45°C oil bath for stirring and reaction for 48 hours. After the reaction is completed and cooled, transfer to a dialysis bag, dialyze with ultrapure water for 48 hours, and freeze-dry to obtain a white powder solid azidation product.

[0070] 5) Pour 750mL DMF into a 1L three-necked flask, heat to 100°C while stirring, and introduce high-purity nitrogen to remove oxygen. After about 1 hour, add 0.366g PMDETA and 0.303g CuBr powder into the flask. Dissolve 0.1g of the above azidation product in 10mL DMF, slowly inject into the three-necked flask after deoxygenation, and continue to react for 24 hours after injection. After the reaction is completed, most of the DMF solvent is evaporated, and the crude product is dialyzed against water for 48 hours. After freeze-drying, a white powder solid is obtained, namely, the cyclic polymer PHEMA.

[0071] 6) Weigh 0.03g of cyclic polymer PHEMA and dissolve it in 0.2mL of anhydrous DMF, then add 0.82g of caprolactone monomer and 3.08mg of Sn(Oct)2, and transfer it into the polymerization reaction tube after it is completely dissolved. After three freeze-pump-thaw cycles, seal the tube and react in an oil bath at 115℃ for 6h. After the reaction, add THF to dilute the product, precipitate with excess cold methanol, centrifuge, repeat this step three times, and vacuum dry to obtain the purified white powder solid P(HEMA-g-PCL). The degree of polymerization of PCL b=28 can be calculated by nuclear magnetic resonance.

[0072] 7) Dissolve 0.2 g of the above white powdery solid P(HEMA-g-PCL) in 5 mL of anhydrous pyridine, stir under nitrogen protection, lower the reaction temperature to 0°C, and then add 75 mg of i BuBr, react at room temperature for 24 hours. After the reaction, the product was precipitated with distilled water, centrifuged, and then dissolved with a small amount of THF and reprecipitated with distilled water. The operation was repeated twice and vacuum dried to obtain the purified product P (HEMA-g-PCL-iBuBr).

[0073] 8) 0.1g P(HEMA-g-PCL-iBuBr) was dissolved in 3mL of a mixed solution of anisole and DMF (1:2, volume ratio), and then 0.25g OEGMA and 0.017g bpy were added. After mixing evenly, the mixture was freeze-pump-thawed three times using an oil pump, and then 0.008g CuBr was quickly added under nitrogen protection, and the freeze-pump-thaw cycle was continued three times. The mixture was sealed and placed in a 60°C oil bath for reaction. The reaction tube was taken out and quenched within the set reaction time, precipitated with excess anhydrous ether, centrifuged, dialyzed with water to remove the copper catalyst and unreacted monomers, and the product was obtained after freeze-drying. The degree of polymerization of OEGMA, c=8, can be calculated by NMR.

[0074] Table 1 Molar ratio of raw materials in each step

[0075]

[0076] Performance Testing:

[0077] The particle sizes of the biodegradable two-sided ring brush polymers prepared in each embodiment and comparative example were tested according to the following method: the two-sided ring brush polymer was prepared into a polymer solution with a concentration of 0.125 mg / mL using phosphate buffer solution (PBS, pH 7.4, ionic strength 150 mM), and then the average particle size of the polymer solution was measured using a dynamic laser light scattering instrument. The specific results are shown in the table below. Among them, the measurement results of Example 1 are shown in Figure 2 As shown. Figure 2 It can be seen that the particle size of the polymer prepared in Example 1 is 34 nm.

[0078] The biodegradable two-sided ring brush polymers prepared in each embodiment and comparative example were subjected to drug physical embedding tests. The specific experimental process, calculation method of drug encapsulation efficiency and drug loading rate refer to the literature (Tu Xiaoyan, Liu Wenxia, ​​Wei Hua. Synthesis and self-assembly of core-shell-crown structured amphiphilic cyclic brush copolymers. Polymer Materials Science and Engineering, 2020, 36(7): 23-30.).

[0079] Table 2 Structure and performance test results of various embodiments and comparative examples

[0080] m n p Particle size, nm Drug loading rate, % Encapsulation rate, % Example 1 28 8 8 34 8.90 89.25 Example 2 10 12 2 30 8.62 84.50 Example 3 50 5 15 42 7.84 79.02 Example 4 42 20 3 40 8.10 80.83 Comparative Example 1 5 8 8 30 4.60 40.36 Comparative Example 2 28 25 8 43 5.72 55.86 Comparative Example 3 28 8 20 40 6.05 59.55 Comparative Example 4 28(b) 8(a) 8(c) 30 4.20 40.88

[0081] It can be seen from the data in the above table that the particle sizes of Examples 1 to 4 and Comparative Examples 1 to 4 are all between 30 and 50 nm, but the drug loading rate and encapsulation rate of the embodiments are significantly higher than those of the comparative examples, wherein the drug loading rate reaches more than 7.80%, and the encapsulation rate reaches more than 79.00%. This is mainly because the hydrophobic structure in the biodegradable two-sided ring brush-shaped polymer micelles is mainly on the annular core, with a larger space, which can encapsulate more drugs. At the same time, the hydrophilic brush-shaped segments on the side chains have better hydrophilicity, which can prevent the polymer molecules from aggregating, thereby better protecting the drugs and making them less likely to fall off.

[0082] The above embodiments are typical examples listed to illustrate the technical solutions of the present invention in detail. The present invention is subject to the protection scope of the claims and the content of the invention and is not limited by the implementation scheme. Simple replacement or modification of the present invention is still within the protection scope of the present invention.

Claims

1. A biodegradable double-sided brush polymer, characterized in that: It has the structure shown in formula I: Among them, m=a natural number from 10 to 50, n=a natural number from 5 to 20, and p=a natural number from 2 to 15.

2. A method for preparing a biodegradable double-sided brush polymer, characterized in that: The steps include: Step 1, propargyl alcohol and caprolactone undergo a ring-opening polymerization reaction to generate a polymer shown in formula II; Step 2, the polymer represented by formula II is subjected to substitution reaction with 2-bromoisobutyryl bromide to generate a polymer represented by formula III; Step 3, the polymer represented by formula III is subjected to an atom transfer radical polymerization reaction with 2-hydroxyethyl methacrylate to generate a polymer represented by formula IV; Step 4, the polymer represented by formula IV is subjected to an azidation reaction with sodium azide to generate a polymer represented by formula V; Step 5, the polymer represented by formula V is subjected to a click chemistry reaction to generate a polymer represented by formula VI; Step 6, the polymer represented by formula VI is subjected to a substitution reaction with 2-bromoisobutyryl bromide to generate a polymer represented by formula VII; Step 7, atom transfer radical polymerization of the polymer represented by formula VII and oligo(ethylene glycol methoxymethylacrylate) to generate a biodegradable two-sided ring brush polymer represented by formula I; Among them, m = natural number from 10 to 50, n = natural number from 5 to 20, p = natural number from 2 to 15 。 3. The preparation method according to claim 2, characterized in that: In step 1, under anaerobic conditions, propargyl alcohol and caprolactone undergo a ring-opening polymerization reaction in the presence of a catalyst; preferably, the molar ratio of propargyl alcohol, caprolactone and the catalyst is 1:15-60:0.02-0.1; more preferably, the catalyst is stannous octoate, stannous isooctanoate or tetraphenyltin.

4. The preparation method according to claim 2, characterized in that: In step 2, the polymer represented by formula II is subjected to substitution reaction with 2-bromoisobutyryl bromide under alkaline conditions, wherein the molar ratio of the polymer represented by formula II, the base and 2-bromoisobutyryl bromide is 1:4-16:3-12; preferably, the base is a weak organic base; more preferably, the base is triethylamine or pyridine.

5. The preparation method according to claim 2, characterized in that: In step 3, under anaerobic conditions, the polymer represented by formula III and 2-hydroxyethyl methacrylate are subjected to an atom transfer radical polymerization reaction in the presence of a catalyst, wherein the catalyst comprises CuBr and a ligand, wherein the ligand is selected from 2,2′-bipyridine or tris(2-dimethylaminoethylamine); preferably, the molar ratio of the polymer represented by formula III, 2-hydroxyethyl methacrylate, 2,2′-bipyridine and CuBr is 1:8 to 25:2:1; the molar ratio of the polymer represented by formula III, 2-hydroxyethyl methacrylate, tris(2-dimethylaminoethylamine) and CuBr is 1:8 to 25:1:

1.

6. The preparation method according to claim 2, characterized in that: In step 4, the molar ratio of the polymer represented by formula IV to sodium azide is 1:10-50.

7. The preparation method according to claim 2, characterized in that: In step 5, under anaerobic conditions, the polymer represented by formula V undergoes a click chemistry reaction under the catalysis of N′,N′,N′,N′,N′-pentamethyldiethylenetriamine and CuBr; preferably, the molar ratio of the polymer represented by formula V, N′,N′,N′,N′,N′-pentamethyldiethylenetriamine and CuBr is 1:10-50:10-50.

8. The preparation method according to claim 2, characterized in that: In step 6, the polymer represented by formula VI undergoes a substitution reaction with 2-bromoisobutyryl bromide under alkaline conditions, wherein the molar ratio of the polymer represented by formula VI, the base and 2-bromoisobutyryl bromide is 1:2-8:2-6; preferably, the base is an organic weak base; more preferably, the base is selected from triethylamine or pyridine.

9. The preparation method according to claim 2, characterized in that: In step 7, under anaerobic conditions, the polymer represented by formula VII and oligo(ethylene glycol methoxymethylacrylate) are subjected to atom transfer radical polymerization under the catalysis of 2,2′-bipyridine and CuBr, wherein the molar ratio of the polymer represented by formula VII, oligo(ethylene glycol methoxymethylacrylate), 2,2′-bipyridine and CuBr is 1:5 to 30:2:1.

Citation Information

Patent Citations

  • Biodegradable cross-linked polymer, and preparation method thereof

    CN103709691A

  • Acid-sensitive amphiphilic star-shaped block copolymer as well as preparation method and application thereof

    CN103554508A

  • Cyclopoly(N-vinylcaprolactam) as well as preparation method and application thereof

    CN104558270A

  • Cyclic polycaprolactone-polyethylene glycol amphipathic block copolymer and preparation and applications

    CN107383377A

  • A ring-brush-like zwitterionic polymer based on lubrication and pH responsiveness, its preparation method and application

    CN114933677A